A review of ancillary services in the airline industry - Liu, Honglin; Abdullah, Nawal Hanim; Lee, Shin Yiing (Cogent OA, 2024)
The significance of ancillary services within the airline industry is progressively gaining prominence. As such, research on airlines’ ancillary services has continuously grown. The primary objective of this research article is to provide a review of ancillary services on passengers’ willingness to pay and the personalized pricing within the airline industry, achieved through the analysis of published scholarly works. The examination of published papers has been conducted with diverse criteria, including research methodologies, analytical perspectives, statistical methodologies, thematic coverage, technological dimensions, authorship, and geographical origins. The conclusions suggest a promising future regarding both airlines’ ancillary service applications and research in this area. The most crucial limitation stems from selecting works subject to examination as the analysis dealt with willingness to purchase and personalisation pricing field papers. Additionally, the selected region has not been widely covered. Nonetheless, this article can potentially be valuable for researchers and airline managers as it sheds light on emerging trends within both domains. These trends pertain not only to evolving technologies themselves but also to the novel applications thereof.